Determinants of Firm Value in the Indonesian Banking Sector: A Study on Profitability, Leverage, and Dividend Policy - Rahayu, Dede Sri; Suryanugraha, Dim Zarita; Nugraha, Galih; Bintari, Vivi Indah; Kusnandar, Deasy Lestary (Entrepreneurship Faculty, Universitas Garut, 2025)
This study aims to investigate and provide empirical evidence regarding the influence of profitability, leverage, and dividend policy on firm value. The research population comprises 141 financial data entries collected from 47 companies that were part of the banking sector between 2021 and 2023. The sampling technique employed is purposive sampling. The sample was selected based on the following criteria: (1) companies listed in the banking sector on the Indonesia Stock Exchange (IDX) during 2020–2023; (2) companies with complete financial report data; and (3) companies that consistently distributed dividends throughout 2020–2023. Based on these criteria, the final sample consisted of 60 financial data entries from 20 companies across three observation periods. This study employs a verification analysis method and utilizes panel data regression analysis as its analytical technique. The results of the hypothesis testing indicate that profitability and leverage have a positive effect on firm value, whereas dividend policy does not have a significant impact on firm value. Keywords: Firm Value; Profitability; Leverage; Dividend Policy; Banking Sector